Razumeti razumevanje - Ferbežar, Ina (Jezik in slovstvo, 2008)
Although rather elusive due to its complexity, comprehension is a phenomenon that lies at the very core of humanities. Traditional linguistics does not deal with it in detail, following the assumption that the knowledge of language in itself is sufficient for comprehension. In the paper comprehension is defined as a creation of meaning that depends on factors related to the comprehender, as well as on social and textual factors. Comprehension is schematized as the gradational overlapping of meaning createdby the speaker and the comprehender. Furthermore, theoretical and methodological issues related to the empirical quantification of comprehension are emphasized. ___________________________
Keywords: Slovene; slovenščina; razumevanje; sporazumevanje; psiholingvistika; besediloslovje; Text linguistics; socilingvistika